The role of coordination strength in solid polymer electrolytes: compositional dependence of transference numbers in the poly(ε-caprolactone)–poly(trimethylene carbonate) system. Issue 45 (15th November 2021) - Eriksson, Therese; Mace, Amber; Mindemark, Jonas; Brandell, Daniel
Abstract : A linear dependence of the lithium transference number and the composition of the polyester–polycarbonate copolymer electrolyte host material was discovered, and the coordination properties causing the trend were investigated with DFT calculations. Abstract : Both polyesters and polycarbonates have been proposed as alternatives to polyethers as host materials for future polymer electrolytes for solid-state lithium-ion batteries. While being comparatively similar functional groups, the electron density on the coordinating carbonyl oxygen is different, thereby rendering different coordinating strength towards lithium ions. In this study, the transport properties of poly(ε-caprolactone) and poly(trimethylene carbonate) as well as random copolymers of systematically varied composition of the two have been investigated, in order to better elucidate the role of the coordination strength. The cationic transference number, a property well-connected with the complexing ability of the polymer, was shown to depend almost linearly on the ester content of the copolymer, increasing from 0.49 for the pure poly(ε-caprolactone) to 0.83 for pure poly(trimethylene carbonate). Contradictory to the transference number measurements that suggest a stronger lithium-to-ester coordination, DFT calculations showed that the carbonyl oxygen in the carbonate coordinates more strongly to the lithium ion than that of the ester. FT-IR measurements showed the coordination number to be higher in the polyester system, resulting in a higher total coordination strength and thereby resolving the paradox. This likely originates in properties that are specific of polymeric solvent systems, e.g. steric properties and chain dynamics, which influence the coordination chemistry. These results highlight the complexity in polymeric systems and their ion transport properties in comparison to low-molecular-weight analogues, and how polymer structure and steric effects together affect the coordination strength and transport properties.